The Dynamics of Personality the Main Character Drama Partners Korea 2: Justice for the Study Psychoanalysis Sigmund Freud - Helmi Wicaksono; Khoirul Muttaqin; Maulida Safira Al-Haddar; Ifit Novita Sari (PT ARRUS Intelektual Indonesia, 2023)
This research aims to describe the Id, Ego, and Superego main character Drama Partners for Justice 2 uses the psychological approach of literature. This type of research is qualitative narrative research. The data obtained from this research resulted in a literary psychological analysis found in Drama Partners for Justice 2. There are three psychological structures of someone who's found in literary psychology presented by Sigmund Freud, that Id, Ego, and Superego.